Using meta-analysis to estimate the incidence of Lyme borreliosis clinical manifestations in Denmark, Ireland and Sweden based on publicly-available Lyme neuroborreliosis data - Gordon Brestrich; Madiha Shafquat; Frederick J. Angulo; Alexander Davidson; Ye Tan; Kate Halsby; Julie Davis; Jennifer C Moïsi; James H. Stark (Ticks and Tick-Borne Diseases)
Lyme borreliosis (LB) is the most common tick-borne disease in Europe and can manifest as localized erythema migrans (EM) or further disseminate into Lyme neuroborreliosis (LNB), Lyme arthritis (LA) or other manifestations. However, public health surveillance in Denmark and Ireland only captures LNB, while published LB data for Sweden only includes LNB. To enhance the understanding of LB disease burden in these countries, this study aimed to estimate LB incidence by clinical manifestation using the ratio of each manifestation to LNB. These ratios were derived using random effects meta-analysis of published data from other European countries. We estimated the ratios for EM/LNB, LA/LNB and other manifestations/LNB to be 42.8 (95 % confidence interval [CI]: 36.4–50.4), 0.9 (95 % CI: 0.7–1.0), and 0.8 (95 % CI; 0.4–1.4), respectively. Applying these ratios to the LNB incidence resulted in an estimated overall LB incidence of 151.5 cases per 100,000 population per year (PPY) in Denmark, 285.2 per 100,000 PPY in Sweden and 9.5 per 100,000 PPY in Ireland. These correspond to >36,000 LB cases per year compared to approximately 800 LNB cases reported in these three countries. Furthermore, the estimated incidence of disseminated manifestations was 8.7 and 16.4 per 100,000 PPY in Denmark and Sweden, respectively. These estimates across LB manifestations highlight the LB health burden on the national healthcare systems. Future studies that directly estimate the incidence of medically-attended LB from healthcare registries, claims data or administrative medical records may help validate these estimates.